Formation of bainite below the MS temperature: Kinetics and crystallography. (15th February 2016) - Samanta, Santigopal; Biswas, Pinaki; Giri, Sushil; Singh, Shiv Brat; Kundu, Saurabh
Abstract: Isothermal transformation below the M S temperature has been reported quite some time ago and has been confirmed in the present work. The nature of the transformation product and the mechanism of the transformation have been debated in literature. It has been inferred using existing models of isothermal martensite transformation that the product forming below M S cannot be martensite. The product has been identified as bainite. It has further been shown that the diffusion-controlled growth rate of bainite at such a low temperature is too slow to explain the observed transformation kinetics. On the other hand, the kinetics of isothermal transformation below M S has been shown to be consistent with the model based on the formation of bainite by displacive mechanism. Detailed analysis of crystallographic features of mixed martensite and bainite microstructure was done using electron backscatter diffraction (EBSD) and mathematical modelling. It has been shown that the crystallographic features of martensite and the bainite formed below M S are exactly the same; these include orientation relationship, habit planes, displacement directions and the shape deformation. It has also been shown that bainite poles can get shifted due to plastic accommodation of austenite caused by martensite laths. The shift was predicted accurately using crystal plasticity and theory of variant selection. All these results lead to the conclusion that bainite forms by a displacive mechanism of transformation. Graphical abstract: